Small Cyclic Diglycolamides: Tautomerism, Solvent Extraction and Coordination with f‑Elements: One Strain to Rule Them All - Kalinin, Mikhail A.; Evsiunina, Mariia V.; Kalle, Paulina; Lyssenko, Konstantin A.; Matveev, Petr I.; Borisova, Nataliya E. (Inorganic chemistry, 2024)
The search for new effective extractants is an important task for the management of high-level liquid waste (HLW) generated during the reprocessing of spent nuclear fuel. Here, we synthesized a series of diglycolamides with cyclic substituents for the first time. We disclosed their coordination with f-element nitrates [La(NO3)3 and UO2(NO3)2] by SC-XRD study and complexation properties toward Am(III), Ln(III), and U(VI) during solvent extraction from nitric acid solutions. Using dynamic nuclear magnetic resonance (NMR) and density functional theory (DFT) calculations, the importance of tautomerism in the extraction properties of diglycolamides was shown.